Microwave assisted synthesis of zinc vanadate nanoparticles and photocatalytic application. (20th January 2020) - Iqbal, M; Fatima, M; Javed, T; Anam, A; Nazir, A; Kanwal, Q; Shehzadi, Z; Khan, M I; Nisar, J; Abbas, M; Naz, S
Abstract: In recent years, the nanotechnology has gained much attention since the nanoparticles (NPs) have applications in every field of life. The hetero-structured are of special interest due to their higher photocatalytic activity. In present investigation, Zinc vanadate NPs were synthesized from vanadium and zinc salts by microwave assisted precipitation method. The Zinc vanadate NPs were characterized by x-ray Powder Diffraction (XRD), Energy-dispersive x-ray spectroscopy (EDX), Scanning electron microscope (SEM) and UV-visible techniques. The photocatalytic activity (PCA) was evaluated by degrading the methylene blue (MB) dye and process variables were optimized. The Zinc vanadate size was <100 nm and particles were in aggregates form. The MB dye degradation was performed at different conditions of process variables and it was observed that MB dye was significantly degraded using Zinc vanadate NPs under UV light irradiation. The reaction time, catalyst dose and dye initial concentration showed variable effect on dye degradation. Based on results, it can be concluded that the microwave irradiation is viable for the synthesis of Zinc vanadate NPs for photocatalytic activity. In view of promising efficiency of Zinc vanadate NPs, it can be used for the dye degradation and for the remediation of textile effluents.